2021
DOI: 10.1016/j.bj.2020.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy in older patients with cancer

Abstract: Ageing implicates a remodeling of our immune system, which is a consequence of the physiological senescence of our cells and tissues coupled with environmental factors and chronic antigen exposure. An immune system that senesces includes more differentiated cells with accumulation of highly differentiated CD4 and CD8 T cells. The pool of naive T cells decreases with the exponential thymic involution induced by age. Differentiated T cells have similar, if not higher, functional capacities but scarce studies are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 95 publications
0
33
0
Order By: Relevance
“…However, in patients older than 75 years, resistance to anti-PD-1/anti-PD-L1 therapy has been observed in squamous cell carcinoma and adenocarcinoma of the lung, renal cell carcinoma and squamous cell carcinoma of the digestive tract. Nevertheless, two other studies in NSCLC reported the same benefit in the elderly as that seen in younger individuals [99,100].…”
Section: Patient-intrinsic Factors Immunosenescencementioning
confidence: 78%
“…However, in patients older than 75 years, resistance to anti-PD-1/anti-PD-L1 therapy has been observed in squamous cell carcinoma and adenocarcinoma of the lung, renal cell carcinoma and squamous cell carcinoma of the digestive tract. Nevertheless, two other studies in NSCLC reported the same benefit in the elderly as that seen in younger individuals [99,100].…”
Section: Patient-intrinsic Factors Immunosenescencementioning
confidence: 78%
“…The KEYNOTE‐048 trial 7 established pembrolizumab, with or without a chemotherapy backbone, as the new standard of care for metastatic or recurrent head and neck cancer. While there is a dearth of studies specifically for the elderly and frail population, immunotherapy is often considered a good option for this subgroup given its efficacy and lower rate of toxicities 47 . The KEYNOTE trial was published in 2019, after most of the patients in this study received PCC, which is reflected in the fact that only 6 patients out of 80 received immunotherapy prior to PCC, although 26 patients received subsequent immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…32 Treatment with anti-programmed cell death protein 1 (PD-1)/programmed death-ligand 1 (PD-L1) agents is, therefore, an attractive option for elderly patients with multiple comorbidities. 33 Pooled data on elderly patients (aged 75 years and above) with PD-L1-positive advanced nonsmall-cell lung cancer (NSCLC) from three landmark cancer trials were recently analyzed. 34 Results demonstrated that immunotherapy improved overall survival in these patients compared with chemotherapy, and results were comparable to the overall population results in the individual studies.…”
Section: Cancer Patientsmentioning
confidence: 99%